2022
DOI: 10.1002/lary.30327
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Nasal Mucosal Temperature and Nasal Patency—A Computational Fluid Dynamics Study

Abstract: Objectives Recent evidence suggests that detection of nasal mucosal temperature, rather than direct airflow detection, is the primary determinant of subjective nasal patency. This study examines the role of nasal mucosal temperature in the perception of nasal patency using in vivo and computational fluid dynamics (CFD) measurements. Methods Healthy adult participants completed Nasal Obstruction Symptom Evaluation (NOSE) and Visual Analogue Scale (VAS) questionnaires. A temperature probe measured nasal mucosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Many research studies have shown a lack of correlation between nasal resistance and sensation of nasal airflow. 24,31,32 In fact, today the leading hypothesis is that the primary mechanism of nasal airflow sensation is the stimulation of TRPM8 cold receptors, [3][4][5][6][7][8][9][10][11][12][13][14][15] which was not investigated in past studies of mucosal decongestion.…”
Section: Discussionmentioning
confidence: 99%
“…Many research studies have shown a lack of correlation between nasal resistance and sensation of nasal airflow. 24,31,32 In fact, today the leading hypothesis is that the primary mechanism of nasal airflow sensation is the stimulation of TRPM8 cold receptors, [3][4][5][6][7][8][9][10][11][12][13][14][15] which was not investigated in past studies of mucosal decongestion.…”
Section: Discussionmentioning
confidence: 99%
“…It can be deduced that the same sensors that cause subjective sensing of nasal patency are responsible for subjective sensing of heat exchange between the nasal airflow and the nasal tissue, and several studies have demonstrated correlations between mucosal cooling and temperature, obtained from CFD simulations, and patients’ subjective evaluation of nasal patency [ 50 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Part I—computational Rhinologymentioning
confidence: 99%
“…This spurs optimism towards predicting subjective sensation of nasal patency through CFD simulations, adding clinical value to virtual surgery. However, it has been pointed out by several authors that the subjective sensing of nasal patency might not be a measure of the objective flow resistance, but rather the cooling effect of the nasal mucosa [ 68 ]. In this case, CFD must be correlated with subjective measures, directly, because no in vivo measurements exist to measure mucosal temperature or heat flux.…”
Section: Part I—computational Rhinologymentioning
confidence: 99%
“…In fact, nowadays, ear, nose and throat (ENT) surgeons routinely take their surgical decisions mostly based on the analysis of computed tomography (CT) scans, which provide a detailed view of the anatomy of the nasal cavities. In principle, the nose flow can be well described by CFD, which is indeed increasingly useful to support ENT doctors in their diagnosis (Moreddu et al 2019;Tjahjono et al 2023) and to improve our understanding of the complex physics of the nose flow (Calmet et al 2019;Farnoud et al 2020). Yet, the basic questions routinely asked by ENT doctors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the nose flow can be well described by CFD, which is indeed increasingly useful to support ENT doctors in their diagnosis (Moreddu et al. 2019; Tjahjono et al. 2023) and to improve our understanding of the complex physics of the nose flow (Calmet et al.…”
Section: Introductionmentioning
confidence: 99%